Musculoskeletal decline and mortality: prospective data from the Geelong Osteoporosis Study. Issue 3 (26th December 2016) - Pasco, Julie A.; Mohebbi, Mohammadreza; Holloway, Kara L.; Brennan‐Olsen, Sharon L.; Hyde, Natalie K.; Kotowicz, Mark A.
Abstract: Background: We aimed to examine the relationship between musculoskeletal deterioration and all‐cause mortality in a cohort of women studied prospectively over a decade. Methods: A cohort of 750 women aged 50–94 years was followed for a decade after femoral neck bone mineral density (BMD) and appendicular lean mass (ALM) were measured using dual energy X‐ray absorptiometry, in conjunction with comorbidities, health behaviour data, and other clinical measures. The outcome was all‐cause mortality identified from the Australian National Deaths Index. Using Cox proportional hazards models and age as the time variable, mortality risks were estimated according to BMD groups (ideal‐BMD, osteopenia, and osteoporosis) and ALM groups ( T ‐scores > −1.0 high, −2.0 to −1.0 medium, <−2.0 low). Results: During 6712 person years of follow‐up, there were 190 deaths, the proportions increasing with diminishing BMD: 10.7% (23/215) ideal‐BMD, 23.5% (89/378) osteopenia, 49.7% (78/157) osteoporosis; and with diminishing ALM: 17.0% (59/345) high, 26.2% (79/301) medium, 50.0% (52/104) low. In multivariable models adjusted for smoking, polypharmacy, and mobility, compared with those with ideal BMD, mortality risk was greater for those with osteopenia [hazard ratio (HR) 1.77, 95% confidence interval (CI) 1.11–2.81] and osteoporosis (HR 2.61, 95%CI 1.60–4.24). Similarly, compared with those with high ALM, adjusted mortality risk was greater for medium ALM (HR 1.36, 95%CI 0.97–1.91) and low ALM (HR 1.65, 95%CI 1.11–2.45). When BMD and ALM groups were tested together in the model, BMD remained a predictor of mortality (HR 1.74, 95%CI 1.09–2.78; HR 2.82, 95%CI 1.70–4.70; respectively), and low ALM had borderline significance (HR 1.52, 95%CI 1.00–2.31), which was further attenuated after adjusting for smoking, polypharmacy, and mobility. Conclusions: Poor musculoskeletal health increased the risk for mortality independent of age. This appears to be driven mainly by a decline in bone mass. Low lean mass independently exacerbated mortality risk, and this appeared to operate through poor health exposures.